O tráfico lícito no atlântico - importação de idéias no Brasil oitocentista: legado luso, desdobramentos e a relevância do cientificismo nos debates das elites dirigente e intelectual da geração de setenta - Cunha, Jaeder Fernandes (2008)
Fascinated by the continent where the caravels came from, the Brazilian dominant class was always seduced by the overseas culture, since it had been formed by the models of the colonizers. The XIX century was the one in which the national Brazilian state was constituted, but with it, lots of issues had also to be faced. In Brazil, philosophy was a luxury only for the elite and, along with it, the distorted transformations of the current model at that time: the traffic across the Atlantic. For decades, living souls were illegally traded, although the more intellectualized minds adopted most of the times concomitantly, a more civilized practice, which was the import of ideas. The philosophical systems and nuances were many and varied here, which form the scope of this research; in other words, their identification and historical contextualization. To develop the research analysis, an internal approach was followed, as well as the empirical collection of data for verification in documents which described debates in official publications, proceedings, sentences and parliamentary discourses. The result was the verification of hot debates in several moments, especially in the so-called seventies generation , which treated a broad range of themes, among them, the state secularization and the education reform, both contextualized by the fashion reforms promoted by the typical European scientificism in the XIX century